Baseline assessment of microplastics in commercially important marine bivalves from New York, U.S.A. (March 2023) - Minder, Mackenzie L.; Colombo, Isabella G.; Rountos, Konstantine J.
Abstract: Microplastic (MP) contamination in bivalve mollusks has become a significant concern over the last few years. These ecologically and economically valuable species are popular seafood items for human consumption. As filter feeders, bivalves may ingest MPs in their bodies, possibly impacting their physiology and fitness. Additionally, a considerable amount of the seafood that humans consume comes from coastal areas where MP concentrations tend to be the highest. This research provides the first examination of MPs in eastern oysters ( Crassostrea virginica ) and hard clams ( Mercenaria mercenaria ) that were grown locally in coastal areas of New York, contributing to a baseline for the northeast and mid-Atlantic regions of the U.S. A total of 48 eastern oysters ( n = 12 per site, at four sites) and hard clams ( n = 24 per site, at two sites) were sampled in summer 2021. While MP fibers and fragments (i.e. polyethylene terephthalate, polystyrene, and polypropylene) were found in some oysters, other contaminants (e.g. indigo dye, phthalocyanine, dye 823, etc.) were found in both bivalve species. Particle composition was verified using Raman microspectroscopy. Although mean MP concentrations were low in eastern oysters (i.e. 0.008 MPs g −1 of soft tissue wet weight; 0.125 MPs ind −1 ) and not found in hard clams, more research is needed to assess the magnitude of contamination in these edible bivalves. Highlights: First study of microplastics in two commercial bivalve species in Northeast USA Oysters ( Crassostrea virginica ) and clams ( Mercenaria mercenaria ) were assessed. Microplastic concentrations in oysters were low (0.008 microplastics g −1 ). No microplastics were found in clams. Microplastic concentrations in these bivalves are lower than those in other regions.